2016
DOI: 10.3389/fnhum.2016.00282
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Neuropsychological Abilities in a Large Sample of Patients with Multiple Sclerosis: A Two-Year Longitudinal Study

Abstract: Objective: In this longitudinal study, we monitored two large groups of multiple sclerosis (MS) patients and healthy controls (HC) for 2 years, with the aim of comparing their neuropsychological profile over time.Method: Three hundred and twenty-two patients with MS and 303 HC were administered the Brief Repeatable Battery of Neuropsychological tests (BRB-N); neuropsychiatric measures were also administered. Two follow-ups were scheduled at 1 and 2 years, respectively.Results: A linear mixed model (LMM) with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…All patients in the study assessed as having “moderate” cognitive impairment had a progressive form of MS and a secondary (organic) psychotic disorder. These findings are in keeping with previous evidence of high levels of cognitive impairment in MS and the more specific finding of Borghi et al 12 , 13 that patients with progressive MS and neuropsychiatric comorbidity such as depression are likely to have lower cognitive assessment scores.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All patients in the study assessed as having “moderate” cognitive impairment had a progressive form of MS and a secondary (organic) psychotic disorder. These findings are in keeping with previous evidence of high levels of cognitive impairment in MS and the more specific finding of Borghi et al 12 , 13 that patients with progressive MS and neuropsychiatric comorbidity such as depression are likely to have lower cognitive assessment scores.…”
Section: Discussionsupporting
confidence: 91%
“…A progressive course of MS, older age, the presence of depression, and less time in education were found to be predictors of a more severe cognitive profile in MS patients. 12 A further study by Borghi et al 13 followed up patients and healthy controls over a 2-year period and found that cognitive abilities typically compromised in the early stages of MS (attention, working memory, speed of information processing, and verbal fluency) are also more vulnerable to progression compared with healthy controls, suggesting a need to identify effective rehabilitation treatments that might counteract this decline over time. Previous literature shows that patients with a psychiatric disorder and MS tend to have a more severe course of their MS than those without psychiatric morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Both PASAT and SDMT are widely used tools to detect cognitive deterioration in MS (López-Góngora et al, 2015). However, PASAT seems more cognitively demanding and appears to be more sensitive to disease progression in a 5 years follow-up period (Borghi et al, 2016). Our results suggest that PASAT performance relies on the integrity of larger number of brain connections than SDMT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, typical cognitive impairment in MS is described as a general cognitive slowdown and mainly involves information processing speed, attention, working memory and executive functions [12,13], which are likely to worsen with the disease evolution [14], typically sparing language and orientation. Furthermore, neglect, acalculia, apraxia agraphia are notably not peculiar of MS patients.…”
Section: Discussionmentioning
confidence: 99%